Electronic Structure Evaluation of an Oxidized Tris(methoxy)‐Substituted Ni Salen Complex. Issue 1 (14th December 2015) - Chiang, Linus; Clarke, Ryan M.; Herasymchuk, Khrystyna; Sutherland, Mathew; Prosser, Kathleen E.; Shimazaki, Yuichi; Storr, Tim
Abstract: The Ni salen complex N, N′ ‐bis(2, 3, 4‐trimethoxysalicylidene)‐1, 2‐cyclohexane‐(1 R, 2 R )‐diamine nickel(II) (1 ), containing ortho ‐, meta ‐, and para ‐methoxy‐substituted phenolate moieties, was prepared. Electrochemical studies revealed that the first oxidation of1 occurs at a similar potential to a previously reported Ni salen complex NiSal t Bu, OMe, employing an ortho ‐ t Bu and para ‐methoxy substitution pattern (M. Orio et al., Angew. Chem. Int. Ed. 2010, 49, 4989), demonstrating the counteracting effects of the methoxy substituent depending on ring location ( ortho / para vs. meta ). The second oxidation occurred at a much lower potential ( E 1/2 2 – E 1/2 1 = 0.11 V) for1, in comparison to NiSal t Bu, OMe, suggesting significant localization of the ligand radical. The one‐electron oxidized form was prepared and studied using a number of experimental and theoretical methods. A localized ligand radical electronic structure was confirmed by the shape and intensity of the NIR bands, which was further verified by the presence of both phenolate and phenoxyl signatures in the resonance Raman spectrum. Theoretical calculations provided insight into the degree of ligand radical localization, and the nature of the low energy bands observed in the Vis/NIR experiment. Overall, the oxidation of1 results in a localized ligand radical complex, with further oxidation processes easily accessible due to resonance stabilization afforded by the methoxy substituents. Abstract : A symmetric tris(methoxy)‐substituted Ni salen complex is oxidized to the ligand radical form. Experimental and theoretical analysis shows that the ligand radical is localized to one side of the molecule due to the resonance‐stabilizing effect of the methoxy substituents.